Ligand Exchange of Colloidal ZnO Nanocrystals from the High Temperature and Nonaqueous Approach - Luo, Jun; Dai, Xingliang; Bai, Sai; Jin, Yizheng; Ye, Zhizhen; Guo, Xiaojun (Nano-Micro Letters, 2013)
Colloidal zinc oxide (ZnO) nanocrystals generated from the high temperature and nonaqueous approache are attractive for use in solution-processed electrical and optoelectronic devices. However, the as-prepared colloidal ZnO nanocrystals by this approach are generally capped by ligands with long alkyl-chains, which is disadvantage for solution-processed devices due to hindering charge transport. Here we demonstrate an effective ligand exchange process for the colloidal ZnO nanocrystals from the high temperature and nonaqueous approach by using n-butylamine. The ligand exchange process was carefully characterized. The thin films based on colloidal ZnO nanocrystals with ligand exchange exhibited dramatically enhanced UV photoconductivity.